Comparing the effectiveness of online and face-to-face teaching and learning methods in an engineering course during and after the COVID-19 pandemic - Diana Che Lat; Doris Asmani Mat Yusof; Nurul Ainain Mohd Salim; Roslizayati Razali (Penerbit Universiti Kebangsaan Malaysia, 2024)
The horrific COVID-19 pandemic that took many lives stunned the entire world. To prevent the extremely hazardous COVID-19 infection, all work, including the teaching and learning process, had to be completed online. In order to make learning and teaching successful and accessible to school and university students, teaching and learning techniques have also undergone a drastic transformation. This is achieved through the use of online platforms. In this study, a case study was conducted based on Engineering Course at one of Malaysian university for three course codes, for three semesters during COVID-19 and two semesters after COVID-19. The three course codes are Soil Engineering, Water and Wastewater Engineering, and Concrete and Steel Design. A comparison of teaching and learning assessment methods during and after COVID-19 semesters is described in this study. The effectiveness of online versus face to face teaching and learning was examined by analyzing the assessment grades of university students involved, with a total of 111 to 283 students every semester. Overall, there was a drastic decrease in assessment grades for semesters that experienced a change in the teaching and learning process from online to face-to-face.